The So-called "Decree of Delos", Again (Jos. AJ 14. 231-32). - Eilers, Claude (Scripta Classica Israelica, 2024)
This note supplements my article in this journal (2005), where argued that the "Decree of Delos" of 49 BCE quoted by Josephus at AJ 14.231-32 is not a decree and cannot be from Delos. Here I point out that the document must be from Ephesus given that its eponym was 'Boiotos' and the eponym at Ephesus for this same year can be shown to be 'Boiotios'.